Non-traditional marks. Special reference to the pattern mark, the position mark, and the colour mark - Maroño Gargallo, María del Mar (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
One of the elements that shows the expansion of the trademark law is the great variety of signs whose registration is admitted as a trademark. This study focuses on three types of signs that are integrated or confused with the appearance of the products: the pattern mark, the position mark and the color mark. These types of marks are an excellent example of the tension between the desire of the economic operators to have attractive elements of differentiation and the need to ensure the free availability in the market of certain elements. Having this into account, we analyze the concept of these non-traditional trademarks and their representation requirements, the main absolute grounds for refusal and the scope of legal protection that they receive once registered.